2011
DOI: 10.1007/s10956-011-9340-1
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Style as a Moderator for Students’ Academic Achievement

Abstract: Parenting styles have always been a crucial factor in influencing all aspects of a person's development. The purpose of this study is to test the structural equation model of academic achievement among the students using parenting styles as a moderator. The sample comprised 493 students from eight schools. Parenting styles are determined using the Parental Authority Questionnaire (Buri in J Pers Assess 57:110-119, 1991). Academic achievement is measured based on the students' performance in the Lower Secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 13 publications
(10 reference statements)
2
23
0
8
Order By: Relevance
“…These analyses show that children with special needs who have authoritative parents function better at school in educational terms compared with those with authoritarian parents. This finding constitutes further evidence of the advantage of authoritative parenting in relation to the children's adaptation and functioning, consistent with a long series of previous relevant findings in this area, showing the positive implications of authoritative parenting on children's development (Dyches, Smith, Korth, Roper & Mandleco, 2012;Eisenberg et al, 2005;Ishak et al, 2012;Spera, 2005;Steinberg et al, 1989;Steinberg et al, 1992;Steinberg, 2001). While the present finding does not rule out the possibility of the inverse connection (positive functioning of children encourages authoritative parenting among parents), its importance is in advancing our understanding of the connection between these variables among children with special developmental features, regarding which the research literature has been lacking (Deault, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…These analyses show that children with special needs who have authoritative parents function better at school in educational terms compared with those with authoritarian parents. This finding constitutes further evidence of the advantage of authoritative parenting in relation to the children's adaptation and functioning, consistent with a long series of previous relevant findings in this area, showing the positive implications of authoritative parenting on children's development (Dyches, Smith, Korth, Roper & Mandleco, 2012;Eisenberg et al, 2005;Ishak et al, 2012;Spera, 2005;Steinberg et al, 1989;Steinberg et al, 1992;Steinberg, 2001). While the present finding does not rule out the possibility of the inverse connection (positive functioning of children encourages authoritative parenting among parents), its importance is in advancing our understanding of the connection between these variables among children with special developmental features, regarding which the research literature has been lacking (Deault, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Por tanto, el autoconcepto académico es la evaluación que hace el sujeto de su propia capacidad para aprender en el contexto escolar (Ishak, Low y Lau, 2011). En la infancia temprana es cuando dichos conceptos se desarrollan, habiendo influencia de los estilos de los padres, que pueden desde promoverlo hasta afectarlo, reflejándose en el rendimiento académico (Duchesne y Ratelle, 2010).…”
Section: Discusión Y Conclusiones 85unclassified
“…Es necesario que padres de familia entiendan qué son los estilos parentales, pero para comprenderlos es necesario definir la práctica de crianza, que no es una más que una conducta o acción de la que se valen los padres para tener una interacción con sus hijos, las cuales son gobernadas por las dimensiones afecto y control (Duchesne y Ratelle, 2010;Clerici y García, 2011); por tanto, los estilos parentales son el conjunto o constelación de dichas conductas y actitudes del adulto, que al ser trasmitidas a los hijos les crea un clima emocional que determinará el desarrollo de su comportamiento y el tipo de vínculo que tendrá con sus padres (Ishak, Low y Lau, 2011;Raya, 2008;Climent, 2009).…”
Section: Discusión Y Conclusiones 85unclassified
“…For instance, among the Asian communities, Besharat, Azizi, and Poursharifi (2011);Borak, Kawser, Haque, and Sharmin (2016) ;Dehyadegary, Yaacob, Juhari, and Talib (2012) ;Parsasirat Montazeri, Yusooff, Subhi, and Nen (2013);and Zahed, Rezaee, Yazdani, Bagheri, and Nabeiei (2016) found that most adolescents raised under democratic parenting style have higher academic success than those from authoritarian and laissez-faire parenting styles while Ishak, Low, and Lau (2012), Kang andMoore (2011), andPong, Johnston, andChen (2010) stated that both democratic and authoritarian parenting styles influence students' academic performance. In Europe, Garcia and Gracia (2009) found significant differences in academic performance among Spaniard children from laissez-faire homes.…”
Section: Introductionmentioning
confidence: 99%